Influence of cold ischemia time on the outcome of kidney transplants from donors aged 70 years and above - a collaborative transplant study report - Echterdiek, Fabian Friedrich; Latus, Joerg; Döhler, Bernd; Schwenger, Vedat; Süsal, Caner (Transplantation, 2021)
Background. - The use of kidney allografts from ≥70-y-old donors has increased persistently over the last 20 y. Prolonged cold ischemia time (CIT) is well known to increase graft failure risk. However, despite their growing importance, no data are available on the impact of CIT, specifically on survival of allografts from ≥70-y-old donors. - Methods. - In total, 47 585 kidney transplantations from expanded criteria donors (ECDs) performed during 2000-2017 and reported to the Collaborative Transplant Study were analyzed. The impact of CIT on 5-y death-censored graft and patient survival was studied for transplantations from <70-y (n = 33 305) and ≥70-y-old ECDs (n = 14 280). - Results. - Compared with the reference of ≤12 h CIT, a CIT of 13-18 h did not increase the risk of graft failure significantly, either for recipients of kidneys from <70-y or from ≥70-y-old ECDs. In contrast, graft failure risk increased significantly when CIT exceeded 18 h, both in recipients of kidneys from <70-y and, more pronounced, from ≥70-y-old ECDs (CIT 19-24 h: hazard ratio [HR] = 1.19 and 1.24; P < 0.001; CIT ≥24 h: HR = 1.28 and 1.32, P < 0.001 and P =0.003, respectively). Within the 18-h CIT interval, additional HLA matching further improved survival of ECD transplants significantly, whereas the negative impact of a prolonged CIT >18 h was stronger in ≥65-y-old recipients and for transplants with multiple HLA mismatches. The influence of CIT on patient survival was less pronounced. - Conclusions. - CIT, as long it is kept ≤18 h, has no significant impact on survival of kidney transplants, even from ≥70-y-old ECDs.